Strategi Penanggulangan Bencana Banjir di Kelurahan Rancabolang - Firlya Nuzsa Miyori; Ivan Chofyan (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Indonesia is a country with a relatively high disaster risk. Flood disaster is one of the disasters that often hit various regions in Indonesia. In general, flooding can be caused by high rainfall intensity, low soil infiltration capacity, and the like. The city of Bandung is one of the areas that is often hit by floods. One area in the city of Bandung that is prone to flooding is Rancabolang Village, Gedebage District. This study aims to determine the dominant factors that cause flooding and to formulate strategies related to flood disaster management in Rancabolang Village. This study used a combined method with primary and secondary data collection techniques. The analytical method used in processing research data is multiple linear regression analysis to determine the dominant factors causing flooding and SWOT analysis to formulate a flood disaster management strategy in Rancabolang Village. Based on the results of multiple linear regression analysis, it is known that the factors that influence the height of the inundation are the intensity of rainfall, water infiltration, rivers, and flood control buildings with the dominant factor being problems in flood control buildings. The results of the SWOT formulation in formulating an alternative strategy for dealing with floods in Rancabolang Sub-District are improving and optimizing the quality, quantity and maintenance of flood control buildings, increasing monitoring and evaluation related to drainage systems, and carrying out other programs related to water absorption efforts. Abstrak. Indonesia merupakan salah satu negara dengan risiko bencana yang cukup tinggi. Bencana banjir merupakan salah satu bencana yang seringkali melanda berbagai wilayah di Indonesia. Umumnya banjir dapat disebabkan oleh tingginya intensitas curah hujan, rendahnya kemampuan infiltrasi tanah, dan sejenisnya. Kota Bandung termasuk salah satu wilayah yang seringkali dilanda bencana banjir. Salah satu wilayah di Kota Bandung yang rawan terhadap banjir adalah Kelurahan Rancabolang, Kecamatan Gedebage. Penelitian ini ditujukan untuk mengetahui faktor dominan penyebab banjir dan merumuskan strategi terkait penanggulangan bencana banjir di Kelurahan Rancabolang. Penelitian ini menggunakan metode gabungan dengan teknik pengumpulan data primer dan sekunder. Metode analisis yang digunakan dalam mengolah data penelitian adalah analisis regresi linier berganda untuk mengetahui faktor dominan penyebab banjir dan analisis SWOT untuk merumuskan strategi penanggulangan bencana banjir di Kelurahan Rancabolang. Berdasarkan hasil analisis regresi linier berganda, diketahui bahwa faktor yang berpengaruh terhadap tinggi genangan adalah faktor intensitas curah hujan, peresapan air, sungai, dan bangunan pengendali banjir dengan faktor dominan berupa permasalahan pada bangunan pengendali banjir. Hasil rumusan SWOT dalam merumuskan strategi alternatif penanggulangan bencana banjir di Kelurahan Rancabolang adalah dengan meningkatkan dan mengoptimalkan kualitas, kuantitas serta pemeliharaan pada bangunan pengendali banjir, meningkatkan monitoring dan evaluasi terkait sistem pengaliran, dan melakukan program-program lain yang terkait dengan upaya peresapan air.